In Vitro Macrophage Assay Predicts the In Vivo Anti-inflammatory Potential of Exosomes from Human Mesenchymal Stromal Cells - Pacienza, Natalia Alejandra (2019)
Extracellular vesicles (EVs) play key roles in cell biology and may provide new clinical diagnostics and therapies. However, it has proven difficult to develop protocols for their purification and characterization. One of the major barriers in the field has been a lack of convenient assays for their bioactivity. Developing assays has not been a trivial matter, because of the heterogeneity of EVs, the multiple activities they demonstrate, and the uncertainty about their modes of action. Therefore, it is likely that multiple assays for their activities are needed. One important assay will be for the anti-inflammatory activity observed in mice after administration of the small EVs commonly referred to as exosomes. We developed an assay for the anti-inflammatory activity of exosomes with a line of mouse macrophages. The assay makes it possible to rank different preparations of exosomes by their anti-inflammatory activity, and their ranking predicts their efficacy in suppressing LPS-stimulated inflammation in mice. The assay is convenient for comparing multiple samples and, therefore, should be useful in developing protocols for the purification and characterization of anti-inflammatory exosomes.